2012
DOI: 10.1109/tvcg.2012.215
|View full text |Cite
|
Sign up to set email alerts
|

Does an Eye Tracker Tell the Truth about Visualizations?: Findings while Investigating Visualizations for Decision Making

Abstract: For information visualization researchers, eye tracking has been a useful tool to investigate research participants' underlying cognitive processes by tracking their eye movements while they interact with visual techniques. We used an eye tracker to better understand why participants with a variant of a tabular visualization called 'SimulSort' outperformed ones with a conventional table and typical one-column sorting feature (i.e., Typical Sorting). The collected eye-tracking data certainly shed light on the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 43 publications
0
35
0
2
Order By: Relevance
“…Kim et al (2012) found long periods of eye fixation in top-left areas of the screen in Typical Sort, while eye fixation in SimulSort was of shorter duration. These results suggest that Typical Sort may have caused subjects to overweight the importance of maximally valued objects along only a few attributes on the left of the screen, while SimulSort encouraged patterns of quick browsing.…”
Section: [Figure 4 -Intermediate Object Selection -About Here]mentioning
confidence: 85%
See 3 more Smart Citations
“…Kim et al (2012) found long periods of eye fixation in top-left areas of the screen in Typical Sort, while eye fixation in SimulSort was of shorter duration. These results suggest that Typical Sort may have caused subjects to overweight the importance of maximally valued objects along only a few attributes on the left of the screen, while SimulSort encouraged patterns of quick browsing.…”
Section: [Figure 4 -Intermediate Object Selection -About Here]mentioning
confidence: 85%
“…Indeed, in a complementary paper to this one, Kim et al (2012) 10 used eye-tracking to investigate another group of subjects' browsing behavior in the same decision task, with Typical Sort and SimulSort (i.e., the Visual Sort treatment). Kim et al (2012) found long periods of eye fixation in top-left areas of the screen in Typical Sort, while eye fixation in SimulSort was of shorter duration.…”
Section: [Figure 4 -Intermediate Object Selection -About Here]mentioning
confidence: 99%
See 2 more Smart Citations
“…Visualization analysis often requires keeping several pieces of information in mind while solving a task, so it is possible that the hypothesis does not hold for some tasks, as Kim et al found [30]. In this case, it is still valuable to understand which visual information is inspected and needed to answer a task, even if it is difficult to infer deeper cognitive processes of the person.…”
Section: Imposing On the Usermentioning
confidence: 99%